2006
DOI: 10.1093/ndt/gfl037
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum albumin level before initiating haemodialysis and angiographic severity of coronary atherosclerosis in end-stage renal disease patients

Abstract: Hypoalbuminaemia at the initiation of dialysis is an important predictor of advanced CAD, particularly in male and in diabetic patients. It may reflect mainly a state of inflammation. However, malnutrition as a confounding factor cannot be entirely excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 29 publications
6
22
1
Order By: Relevance
“…Kalantar-Zadeh et al [16] showed an association between serum albumin level and CVD in hemodialysis patients and stated that hypoalbuminemia could be a strong predictor of mortality in dialysis patients. Similar results were obtained by Joki et al [17] who demonstrated that patients in predialysis chronic renal failure with carotid plaque had lower serum albumin level and that hypoalbuminemia was an excellent reflection of cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 88%
“…Kalantar-Zadeh et al [16] showed an association between serum albumin level and CVD in hemodialysis patients and stated that hypoalbuminemia could be a strong predictor of mortality in dialysis patients. Similar results were obtained by Joki et al [17] who demonstrated that patients in predialysis chronic renal failure with carotid plaque had lower serum albumin level and that hypoalbuminemia was an excellent reflection of cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies show that hypoalbuminemia may result from inflammation and contribute to morbidity in chronic renal patients, constituting an important predictor of coronary heart disease. [37,38] A possible implication of cystatin C in the inflammation procedure was also seen by the highly significant correlation with CRP. The mechanism that could explain this correlation may be that during vascular injury in HD patients, the increased production of inflammatory CRP and cytokines stimulate the production of elastolytic cysteine proteases.…”
Section: Discussionmentioning
confidence: 91%
“…As a surrogate marker of the nutritional status and malnutrition, this parameter represents a powerful risk factor for atherosclerotic disease combined with chronic inflammation in patients with CKD 24) . We previously identified a significant inverse relationship between the angiographic severity of coronary atherosclerosis and the BMI values among patients newly treated with hemodialysis 25) . Based on these findings, dyslipidemia, malnutrition and inflammation are potential modifiable factors for retarding the progression of coronary atherosclerosis in patients with conservative CKD.…”
Section: Discussionmentioning
confidence: 99%